Simple current-mode square-rooting circuit with temperature compensation using only OTAs - Tangsrirat, Worapong; Prasertsom, Danucha; Pukkalanun, Tattaya; Surakampontorn, Wanlop (My University, 2010)
A simple current-controlled current-mode square-rooting circuit with temperature compensation employing operational transconductance amplifi ers (OTAs) as active elements is proposed. It has been designed by using only four OTAs, without the employment of additional passive elements. The current gain of the proposed circuit can be electronically controlled, thanks to the tuning property of the OTA. Simulation and experimental results are obtained to verify the theoretical analysis of the proposed circuit technique.
Keywords: Current-mode circuit; Operational transconductance amplifier (OTA); Square-rooting circuit; Temperature compensation